Rheology properties of bitumen binders with various fillers - Alekseenko, Viktor; Verkhoturova, Elena; Zhitov, Roman; Nebratenko, Dmitry (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction: The resistance of road surfaces to the formation of a longitudinal wear mark from passing vehicles at the present stage is one of the most pressing problems in the field of asphalt concrete coatings. Therefore, the search for a solution to this problem constantly continues, including studying the behavior of various components of asphalt concrete mixtures when they are loaded. Methods: The studies were carried out under static load in three temperature modes: 25°C, 40°C and 50°C, as well as using the standard DSR (dynamic shear rheometer) method at temperatures above 70°C. Two types of bitumen were used as binders: semi-blown petroleum road bitumen BND 100/130 and polymer bitumen binder PmB 90. Various fine fillers were introduced into their composition: marble dust, rubber crumbs and modified powder obtained by simultaneous grinding of marble with polyethylene. Results: It was found that a fine filler has a stronger effect on creep than a change in the grade of asphalt concrete binder. The lowest creep and the greatest shear resistance in the entire temperature range of measurements were shown by an asphalt binder based on a powder obtained by joint grinding of marble and polyethylene. Conclusions: The effect of a fine filler on the creep of a bitumen binder may exceed the effect associated with a change in the type of bitumen binder. It is obvious that it is the fine filler that has a greater effect on the stability of asphalt concrete to the formation of ruts than conventional semi-blown bitumen binders.